Computational support for the process of software requirement specification - Esteca, Antonio Marcos Neves; Simonato, Arianne; De Souza, Rogéria Cristiane Gratão; Valêncio, Carlos Roberto; Garcia, Rogério Eduardo [UNESP]; Tronco, Mário Luiz; Borges, Vanessa Dos Anjos (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The software industry has become more and more concerned with the appropriate application of activities that composes requirement engineering as a way to improve the quality of its products. In order to support these activities, several computational tools have been available in the market, although it is still possible to find a lack of resources related to some activities. In this context, this paper proposes the inclusion of a module to aid in the requirements specification to a tool called Requirements Elicitation Support Tool. This module allows to specify requirements in accordance with IEEE 830 standard, thus contributing to the documentation of the requirements established for a software system, besides supporting the learning of concepts related to the requirements specification, which improves the skills of users of the tool. © 2012 IEEE.
Keywords: IEEE 830; software quality; software requirements specification; support tool; Computational tools; Requirement engineering; Requirements elicitation; Requirements specifications; Software industry; Software Quality; Software requirement specification; Software requirements specifications; Software systems; Support tool; Computer software selection and evaluation; Information science; Software engineering; Specifications; Requirements engineering